Comparative study of catalytic and non-catalytic steam reforming of bio-oil: Importance of pyrolysis temperature and its parent biomass particle size during bio-oil production process. (15th April 2022) - Xiong, Zhe; Fang, Zhou; Jiang, Long; Han, Hengda; He, Limo; Xu, Kai; Xu, Jun; Su, Sheng; Hu, Song; Wang, Yi; Xiang, Jun
Graphical abstract: Highlights: Bio-oil from biomass with a small particle size can generate more gases. Bio-oil produced with maximum is not suitable for syngas production. Bio-oil with high oligomers produces more tar and aromatic molecular structures. Organic fraction of bio-oil determines the gas yield to a great extent. Bio-oil with low oligomers and high organics is suitable for syngas production. Abstract: This paper investigated the effects of initial bio-oil production conditions (temperature and biomass particle size) on the downstream catalytic and non-catalytic steam reforming of bio-oil. The various bio-oil samples obtained from different pyrolytic temperatures (375, 500, and 580 °C) as well as from different biomass particle sizes (average size from 0.3 to 5.2 mm) were condensed as liquid and then fed into the reforming reactor. The results indicated that the tar yield from the steam reforming decreased significantly by as much as 80% as the original biomass particle size increased from 0.3 to 0.8 mm, but remained almost unchanged for further increasing the particle size up to 5.2 mm. As the biomass particle size increased, the aromatic ring systems in the tars decreased, and the amount of aromatic ring systems in bio-oil tars was much lower than that in biomass tars at the same reforming condition. Additionally, the trends of the effects of bio-oil production temperature and biomass particle size on the tar yields followed the trends of these effects on bio-oil yields, i.e., the higher the bio-oil yield, the higher the tar yield from bio-oil reforming. The tar yields were affected by the amount of oligomers in the bio-oil to a great extent. The gas yields from steam reforming gradually decreased as the biomass particle size increased. The content of oligomers in bio-oil was not the key factor dominating the formation of gases products, while the content of organics in bio-oil determined the gas yields significantly. According to the results, bio-oil produced at higher temperatures (e.g., 580 °C) from biomass with a small particle size (≤0.3 mm) could generate more syngas from steam reforming using the Fe-loaded bio-char catalyst.